Periodic assessment of plasma sFlt-1 and PlGF concentrations and its association with placental morphometry in gestational hypertension (GH) - a prospective follow-up study - Nalliah Sivalingam; Judson John; Nadarajah Vishna; Jeevaratnam Kamalan; Abdullah Mohd (BMC, 2010)
Abstract Background Hypertensive disorders in pregnancy contributes to about 12% of maternal deaths in Malaysia and similarly worldwide. Early detection and adequate management are preventable strategies. Biochemical markers of abnormal angiogenesis would be more specific in early detection than routine blood pressure and proteinuria measurements. The aim of this study was to estimate maternal plasma PlGF and sFlt-1 levels in pregnant women with gestational hypertension at three intervals of pregnancy and correlate these biomarker levels with placental morphometry. Methods Venous blood samples (antepartum, intrapartum and post partum periods) were drawn to estimate for sFlt-1 and PlGF levels while placental tissue samples were examined for placental morphometry. Results PlGF levels were lower in gestational hypertension (GH) compared to normotensive during antepartum and intrapartum period, whereas sFlt-1 levels were elevated in GH at antepartum, intrapartum and postpartum intervals during pregnancy. An inverse relationship between these two biomarkers was observed through correlation analysis. PlGF levels were inversely correlated with total villous surface area of the placental periphery (TCsa-C) and villous capillarization (VC-C) of the placental periphery. Conclusion We established periodic values of for sFlt-1 and PlGF levels for the first time in an ethnically diverse Malaysian setting. We suggest the development of GH in women is related to defective capillarization. In demonstrating periodic changes, this study suggest the possibility of developing GH and other long term health complications as a result of prolonged exposure to sFlt-1. The correlation between PlGF levels and morphometric findings also support possible capillarization defect.